Liberation of recalcitrant cell wall sugars from oak barrels into bourbon whiskey during aging - Jarrad Gollihue (Nature Portfolio, 2018)
Abstract Oak barrels have been used by humans for thousands of years to store and transport valuable materials. Early settlers of the United States in Kentucky began charring the interior of new white oak barrels prior to aging distillate to create the distinctively flavored spirit we know as bourbon whiskey. Despite the unique flavor and cultural significance of “America’s Spirit”, little is known about the wood-distillate interaction that shapes bourbon whiskey. Here, we employed an inverse method to measure the loss of specific wood polysaccharides in the oak cask during aging for up to ten years. We found that the structural cell wall wood biopolymer, cellulose, was partially decrystallized by the charring process. This pyrolytic fracturing and subsequent exposure to the distillate was accompanied by a steady loss of sugars from the cellulose and hemicellulose fractions of the oak cask. Distinct layers of structural degradation and product release from within the barrel stave are formed over time as the distillate expands into and contracts from the barrel staves. This complex, wood-sugar release process is likely associated with the time-dependent generation of the unique palate of bourbon whiskey.